2017
DOI: 10.18544/ep-01.16.01.1660
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Słowa kluczowe cukrzyca, wiedza zdrowotna, zachowania prozdrowotne, dzieci Streszczenie Wstęp. Obserwuje się narastającą liczbę nowych zachorowań na cukrzycę typu 1 u dzieci i młodzieży. Choroba ta stwarza wiele problemów związanych z jej przebiegiem, długotrwałością leczenia oraz koniecznością samokontroli. W leczeniu chorób o przewlekłym przebiegu edukacja terapeutyczna uzupełnia i wspomaga prowadzoną terapię. Najważniejszym celem edukacji jest przekazanie informacji o chorobie, ale także wpływ na zachowania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…T1DM entails many extra duties and restrictions for a child, requires self-discipline and self-control in daily monitoring of glu- [15]. Holistically speaking, physical activity is an important stimulator or proper development of children and teenagers and a major factor reducing the risk of cardiovascular diseases, cancers and mortality rates [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…T1DM entails many extra duties and restrictions for a child, requires self-discipline and self-control in daily monitoring of glu- [15]. Holistically speaking, physical activity is an important stimulator or proper development of children and teenagers and a major factor reducing the risk of cardiovascular diseases, cancers and mortality rates [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Their study has shown that such children were inadequately prepared for a healthy lifestyle. The study participants demonstrated a lower level of healthy behaviour, especially in terms of physical activity, self-control, diet and the duration of sleep [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jasione montana L. (Campanulaceae) is a common biennial plant, with ethnopharmacological report indicates its use in sleep disorders in children 1 . Because our previous study showed significant cytotoxic activity of the Et 2 O fraction (JM4), we decided to evaluate on human melanoma cells (CRL-1585) the apoptosis induction ability of JM4 (25-100 μg/mL) and its main compound 22 (25 μg/mL) assessed as luteolin based on the LC-MS phytochemical profile.…”
mentioning
confidence: 99%